Phantom limb pain after lower limb trauma: origins and treatments - Foell, Jens; Bekrater-Bodmann, Robin; Flor, Herta; Cole, Jonathan (International journal of lower extremity wounds, 2011)
Phantom sensations, that is, sensations perceived in a body part that has been lost, are a common consequence of accidental or clinical extremity amputations. Most amputation patients report a continuing presence of the limb, with some describing additional sensations such as numbness, tickling, or cramping of the phantom limb. The type, frequency, and stability of these phantom sensations can vary immensely. The phenomenon of painful phantom sensations, that is, phantom limb pain, presents a challenge for practitioners and researchers and is often detrimental to the patient’s quality of life. In addition to the use of conventional therapies for chronic pain disorders, recent years have seen the development of novel treatments for phantom limb pain, based on an increasing body of research on neurophysiological changes after amputation. This article describes the current state of research in regard to the demographics, causal factors, and treatments of phantom limb pain.
Gesehen am 11.05.2023